Visibility-based zonal communication in massively multi-user online games and distributed simulations - Kazem, Ihab (University of Ottawa (Canada), 2007)
Massively multi-user online games and distributed simulations aim at supporting a large number of users while keeping the communication among the parties synchronous and highly interactive. To achieve collaboration, the virtual world is divided into multiple adjacent hexagonal zones in order to properly organize the entities and efficiently manage their liaison. The data distribution structure is Peer-to-Peer (P2P)-based, to support home users, and is managed by a topology-aware protocol at the application layer rather than the network layer. However, such zoning restricts cross-zonal interactions and exposes the division of the world to the parties. Problems such as crowding one zone among others defeats the very purpose of interest management and makes geographic partitioning alone inefficient for modeling interactions. The objective of the thesis is to introduce the design, implementation, and performance study of an area of interest management approach to manage massively multi-user simulations and online games by shirting messaging from a purely zone-based approach to a visibility-driven one. This makes the partitioning transparent to users. Also, a novel idea is presented for dynamic load balancing to handle transient crowding that can be achieved in real-time without modifying the communication architecture. Implementation and performance measurements are also presented.
Keywords: Engineering, Electronics and Electrical.